The impact of comprehensive healthy lifestyles on obstructive sleep apnea and the mediating role of BMI: insights from NHANES 2005–2008 and 2015–2018 - Jinsong Mou; Haishan Zhou; Shiya Huang; Zhangui Feng (BMC Pulmonary Medicine)
Abstract Objective In this study, the associations between healthy lifestyles and obstructive sleep apnea (OSA) in middle-aged and elderly adults were investigated via data from the National Health and Nutrition Examination Survey (NHANES) for the periods of 2005–2008 and 2015–2018. Methods A total of 6,406 participants aged 40 years and older were included in the analysis. Healthy lifestyle behaviors were assessed through diet quality, physical activity, sleep duration, alcohol consumption, smoking status, and body mass index (BMI). A composite healthy lifestyle score (ranging from 0 to 6) was created and categorized into insufficient (0–2), intermediate (3–4), and optimal (5–6) health groups. Weighted logistic regression models were used to examine the association between these lifestyle scores and OSA, adjusting for some demographic, socioeconomic, and clinical covariates. Additionally, mediation analysis was conducted to evaluate the role of BMI as a mediator in the relationship between the composite healthy lifestyle score and OSA, determining the proportion of the total effect mediated by BMI. Results Participants were classified into insufficient (17.81%), intermediate (56.82%), and optimal (25.37%) lifestyle groups. Higher dietary quality (OR: 0.81, 95% CI: 0.66–0.99) and adequate weight (OR: 0.09, 95% CI: 0.07–0.11) were statistically associated with reduced OSA odds after adjustments, whereas the variables were not. Each one-point increase in the healthy lifestyle score was linked to a 33% reduction in OSA odds (OR: 0.67, 95% CI: 0.63–0.71). A significant linear trend was observed, with better adherence to healthy lifestyle correlating with lower odds of OSA (p for trend < 0.001). Compared with insufficient lifestyle, intermediate lifestyle was linked to a 27% reduction in OSA (OR: 0.73, 95% CI: 0.58–0.91), whereas optimal lifestyle was associated with a 74% reduction (OR: 0.26, 95% CI: 0.21–0.33). Mediation analysis revealed that BMI significantly mediated the relationship between healthy lifestyle score and OSA, accounting for approximately 59.2% of the total effect (P < 0.001). The direct effect of the healthy lifestyle score on OSA remained significant even when controlling for BMI (P < 0.001). Subgroup analyses confirmed consistent benefits across different demographic groups. Conclusions This study revealed that adherence to healthy lifestyles significantly reduces the odds of OSA, with optimal lifestyles leading to a marked decrease in the odds of OSA. Notably, BMI plays a critical mediating role in this relationship. These findings emphasize the importance of promoting healthy lifestyle interventions as a key strategy for the prevention and management of OSA.